ANGPT2 as a Therapeutic Target in Endometriosis: Evolving Perspectives in Angiogenesis - ANGPT2, an Emerging Target in Endometriosis Therapy - Sheeja M J; Kumar B , Sumanth; Muninathan, N; Ramesh Kumar, K.; Jose, Joby P; Jose, Jeena; M, Sreekutty; A M , Jisha; S, Parvathy; V C, Jineesh; K, Sindhu; Sreenivasan, Sreeja; et al. (Biomedical Sciences and Clinical Medicine, 2025)
Endometriosis is a chronic, estrogen-dependent inflammatory condition marked by the ectopic implantation of endometrial-like tissue, most commonly involving the ovaries, peritoneum, and pelvic structures. This ectopic tissue responds to hormonal cycles, leading to symptoms such as pelvic pain, dysmenorrhea, dyspareunia, and infertility. A critical process in the pathophysiology of endometriosis is angiogenesis, which sustains lesion growth and survival. Angiopoietin-2 (Ang-2), encoded by the ANGPT2 gene, is a key regulator of abnormal vascular remodeling in endometriosis, acting as a vascular destabilizer and enhancing angiogenic responses, parti- cularly in conjunction with vascular endothelial growth factor (VEGF). This review synthesizes current evidence on the pathological role of Ang-2 in endometriosis-associated angiogenesis and evaluates its potential as a molecular target for therapy. A comprehensive literature search was performed using PubMed, Scopus, Google Scholar, and Web of Science, covering articles published from 1997 to 2025. Relevant studies were selected based on Ang-2’s involvement in angiogenesis, its expression patterns in endometriotic tissue, and the outcomes of therapeutic interventions. The findings reveal that ANGPT2 expression is upregulated in endometriotic lesions and is modulated by hypoxia, estrogen, and inflammatory factors. Elevated levels of Ang-2 are associated with increased disease severity and vascular immaturity in lesions. Preclinical studies targeting Ang-2, either alone or in combination with VEGF inhibitors, have demonstrated reductions in lesion vascularization and growth, highlighting its therapeutic promise. In conclusion, Ang-2 serves as a critical mediator of pathological angiogenesis in endometriosis and presents a promising target for novel anti- angiogenic therapies. Further translational research and clinical trials are warranted to explore its full therapeutic potential.